1990
DOI: 10.1002/ptr.2650040104
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of juglone

Abstract: The juice of freshly macerated unripe hulls of the black walnut (Juglans nigra) has been used for many years in folk medicine as a treatment for localized, topical fungal infections such as ringworm. It has been proposed that the biological activity of the walnut hulls is due to the presence of the simple naphthoquinone, juglone (5‐hydroxy‐1,4‐naphthoquinone), which has been isolated from the unripe hulls by sublimation. Since the fresh juice of unripe walnut hulls is utilized for the treatment of ringworm, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0
2

Year Published

1994
1994
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 7 publications
1
52
0
2
Order By: Relevance
“…For example, juglone which is produced by walnut trees was found active against a broad spectrum of microorganisms, including bacteria and fungi (Krajci and Lynch, 1978;Dawson and Seymour, 1983;Clark et al, 1990). Rhein which is the most active compound of rhubarb roots was found to have strong antibacterial capacity (Didry et al, 1994).…”
Section: Resultsmentioning
confidence: 99%
“…For example, juglone which is produced by walnut trees was found active against a broad spectrum of microorganisms, including bacteria and fungi (Krajci and Lynch, 1978;Dawson and Seymour, 1983;Clark et al, 1990). Rhein which is the most active compound of rhubarb roots was found to have strong antibacterial capacity (Didry et al, 1994).…”
Section: Resultsmentioning
confidence: 99%
“…Juglone variation in fresh leaves was found within the range of 13.1-1556.0 mg/100 g dry weight on the basis of 1121 trees leaf samples (Thakur & Cahallan, 2011). Juglone is known for its antimicrobial effect (Clark et al, 1990), and it was also reported to decrease the incidence of tumors (Sugie et al, 1998). Phenolics contents in walnut depend on many environmental conditions, genotype of different cultivars (Colarič et al, 2005;Solar et al, 2005), as well as sampling date (Cosmulescu & Trandafir, 2011a,b;Solar et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have shown that juglone has antimicrobial and antifungal effects (25,26). Grover et al, assessed the effect of juglone on planktonic and sessile C. albicans cells.…”
Section: Discussionmentioning
confidence: 99%